2016
DOI: 10.1371/journal.pone.0165449
|View full text |Cite
|
Sign up to set email alerts
|

Consumption Simulations Induce Salivation to Food Cues

Abstract: Salivation to food cues is typically explained in terms of mere stimulus-response links. However, food cues seem to especially increase salivation when food is attractive, suggesting a more complex psychological process. Adopting a grounded cognition perspective, we suggest that perceiving a food triggers simulations of consuming it, especially when attractive. These simulations then induce salivation, which effectively prepares the body for eating the food. In two experiments, we systematically examined the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
81
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 51 publications
(65 reference statements)
9
81
0
1
Order By: Relevance
“…Similarly, work on desire and goals has shown that reading about or seeing chips triggers thoughts about their taste and texture, of eating and enjoying them, and of watching movies with one’s friends (Papies, 2013). Such a cue can also inhibit the competing goal of dieting (Fishbach, Friedman, & Kruglanski, 2003; Papies, Stroebe, & Aarts, 2008a; Stroebe, Mensink, Aarts, Schut, & Kruglanski, 2008), and it increases salivation and the desire to eat (Keesman, Papies, Vermeent, Aarts, & Hafner, 2015), which can lead, for example, to impulsive eating behaviour (see also Hofmann et al, 2008). As this brief analysis has shown, cognitive structures, which are here referred to as situated conceptualisations, mediate the effects of situational cues on health behaviour, and this can explain the effects of habits, impulses, and goals.…”
Section: Mechanisms Of Nonconscious Influences On Health Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, work on desire and goals has shown that reading about or seeing chips triggers thoughts about their taste and texture, of eating and enjoying them, and of watching movies with one’s friends (Papies, 2013). Such a cue can also inhibit the competing goal of dieting (Fishbach, Friedman, & Kruglanski, 2003; Papies, Stroebe, & Aarts, 2008a; Stroebe, Mensink, Aarts, Schut, & Kruglanski, 2008), and it increases salivation and the desire to eat (Keesman, Papies, Vermeent, Aarts, & Hafner, 2015), which can lead, for example, to impulsive eating behaviour (see also Hofmann et al, 2008). As this brief analysis has shown, cognitive structures, which are here referred to as situated conceptualisations, mediate the effects of situational cues on health behaviour, and this can explain the effects of habits, impulses, and goals.…”
Section: Mechanisms Of Nonconscious Influences On Health Behaviourmentioning
confidence: 99%
“…This is often at the cost of long-term investment goals , such as watching one’s weight or controlling one’s alcohol intake for the sake of one’s health later in life. Indeed, the exposure to a tempting stimulus is likely to trigger simulations of consuming and enjoying it (Keesman et al, 2015; Papies, 2013; Simmons, Martin, & Barsalou, 2005), making thoughts of a competing long-term health goal increasingly unlikely (Papies et al, 2008a; Stroebe et al, 2013). In order to improve the nonconscious regulation of health behaviour, situational cues thus need to activate situated conceptualisations of long-term investment goals, rather than of short-term hedonic goals only.…”
Section: Interventions To Affect Nonconscious Regulation Of Health Bementioning
confidence: 99%
“…Those who are frail may not feel » Added water also increases portion size, which can make eating challenging for people with dysphagia who are less likely to be interested in food (Little 2013). » Home-blended meals can be visually unappealing, which means they may not trigger salivation and make swallowing even more difficult (Keesman et al 2016).…”
Section: Lifestyle Causesmentioning
confidence: 99%
“…Pavlovian conditioning is an example of how man is able to acquire several preferences in terms of flavour, which becomes better liked through its association with an already enjoyed taste, nutritive content and positive post-ingestive effect [16]. Pavlovian conditioning is also the cause of "food craving", which is elicited by signs predicting the intake of an appetising food [17]. For instance, in order to perceive the food by the taste or olfactory receptors, aroma and taste components must be released in the saliva, which depends on the food matrix composition and structure and on the masticatory behaviour.…”
Section: Generation Of Aromas and Flavoursmentioning
confidence: 99%